2015
DOI: 10.1039/c5mt00049a
|View full text |Cite
|
Sign up to set email alerts
|

Protective activity of carnosine and anserine against zinc-induced neurotoxicity: a possible treatment for vascular dementia

Abstract: Carnosine (β-alanyl-L-histidine) is a small dipeptide with numerous beneficial effects, including the maintenance of the acid-base balance, antioxidant properties, chelating agent, anti-crosslinking, and anti-glycation activities. High levels of carnosine and its analogue anserine (1-methyl carnosine) are found in skeletal muscle and the brain. Zinc (Zn)-induced neurotoxicity plays a crucial role in the pathogenesis of vascular dementia (VD), and carnosine inhibits Zn-induced neuronal death. Here, the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…Anserine as a biological dipeptide is present in high concentration in human brain and muscles and plays an important role in protection of the nervous system and skeletal muscles showing high antioxidant activity. Carnosine and anserine are expected to have future therapeutic potential in neurodegenerative diseases (29).…”
Section: Nutritional Characteristics Of Ostrich Emu and Rhea Meatmentioning
confidence: 99%
“…Anserine as a biological dipeptide is present in high concentration in human brain and muscles and plays an important role in protection of the nervous system and skeletal muscles showing high antioxidant activity. Carnosine and anserine are expected to have future therapeutic potential in neurodegenerative diseases (29).…”
Section: Nutritional Characteristics Of Ostrich Emu and Rhea Meatmentioning
confidence: 99%
“…As carnosine can chelate Zn 2+ , it is plausible that it binds extracellular Zn 2+ and inhibits Zn 2+ translocation like other chelators. However, our results using a Zn 2+ -sensitive fluorescent dye and RT-PCR indicated that carnosine did not influence [Zn 2+ ] i nor the expression of ZnT-1 [57]. Meanwhile, we demonstrated that carnosine inhibited Zn 2+ -induced upregulation of ER stress-related genes such as GADD34 and CHOP, and attenuated neurodegeneration induced by ER-stressors such as thapsigargin and tunicamycin [57].…”
Section: The Roles Of Carnosine In Protection From Zn 2+ -Induced Neumentioning
confidence: 55%
“…Our DNA microarray analysis demonstrated that Zn 2+ induced a marked upregulation of ER stress-related genes, including CCAAT-enhancer-binding protein homologous protein (CHOP), and growth-arrest and DNA-damage-inducible gene 34 (GADD34) [56,57].…”
Section: Endoplasmic Reticulum (Er) Stress Pathwaymentioning
confidence: 97%
See 2 more Smart Citations